ANALISIS BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA PADA MATERI PELUANG DITINJAU DARI GENDER SISWA KELAS XI IPA SMA NEGERI 1 KOTA BANJARBARU KALIMANTAN SELATAN - Nina Nurmasari; Tri Atmojo Kusmayadi; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract: This research used qualitative approach which aims to describe the factors of student’s creative thinking in mathematical problem solution on probability for male students and female students. The methods used in this study were interviews and tests. The data validation has done by triangulation. The data was obtained from interviews and tests of creative thinking skills in mathematics learning. This tests was composed of five categories: fluency, flexibility, originality, elaboration, and redefinition which are the factors of the creativity. The research was conducted in SMA Negeri 1 Banjarbaru City, South Kalimantan in October until November 2013. The task-based interviews and tests were conducted to collect data from the 11th grade students of SMA Negeri 1 Banjarbaru City, South Kalimantan grade XI Program IPA. Selection of subjects was based on male student and female student. Snowball method was used to determine subject research. Subjects were seven students grade XI Program IPA on SMA Negeri 1 Banjarbaru City, South Kalimantan academic year 2013/2014. The result showed that the male students had the factors of creative thinking ability on fluency, flexibility, originality, and redefinition. The male students did not have enough the factor of creative thinking ability on elaboration. The female students had the factors of creative thinking ability on fluency, flexibility and originality. The female students did not have the factors of creative thinking ability on elaboration and redefinition.Keywords: student’s creative thinking, factors of creative thinking, gender.